Clinical Practice Issues for Liver Transplantation in COVID-19 Recovered Recipients. (June 2022) - Shetty, Kirti; Lominadze, Zurabi; Saharia, Kapil; Challa, Suryanarayana Reddy; Montenegro, Maria; Meier, Raphael P. H.; Malik, Saad; Alvarez-Casas, Josue; Sakiani, Sasan; Jakhete, Neha; Urrunaga, Nathalie; Gray, Stephen H.; et al.
The ongoing burden of COVID-19 in persons with end stage liver failure necessitates the development of sound and rational policies for organ transplantation in this population. Following our initial experience with two COVID-19 recovered recipients who died shortly after transplant, we adjusted our center policies, re-evaluated outcomes, and retrospectively analyzed the clinical course of the subsequent seven COVID-19 recovered recipients. There were two early deaths and 5 successful outcomes. Both deceased patients shared common characteristics in that they had positive SARS-CoV2 PCR tests proximal to transplant (7-17 days), had acute on chronic liver failure, and suffered thromboembolic phenomena. After a careful review of clinical and virological outcome predictors, we instituted policy changes to avoid transplantation in these circumstances. We believe that our series offers useful insights into the unique challenges that confront transplant centers in the COVID-19 era and could guide future discussions regarding this important area.